Fear of HIVsusceptibility influencing burden of care among nurses in South-East NIgeria (2013)
HIV/AIDS currently is a major cause of disability and mortality especially in sub-Saharan Africa. As the population affected by HIV/AIDS increases, so does the burden of this chronic disease and the challenges associated with caring. HIV scourge in Nigeria has been overwhelming since 1992 with debilitating impacts and this study presents the extent of fear of susceptibility and the level of caregivers burden among Nigerian nurses. To direct the study, three special objectives and one hypothesis were raised, which were to determine the extent of fear of susceptibility and perceived seriousness of HIV, to ascertain the percentage of nurses who tested to know their HIV status and the associated level of caregivers burden among nurses. The study also determined the relationship between fear of susceptibility and caregiver’s burden. A purposive sampling technique was used to select 210 nurses caring for people living with HIV/AIDS in the University of Calabar Teaching Hospital, Nigeria. Structured questionnaires and relevant validated scales such as Zarit Burden Interview [1] and abridged Champion Health Belief Model Scale [2] were used to elicit data. Results revealed that the majority of 41.0% respondents nursed fear of susceptibility despite the practice of universal precaution and perceived HIV as a serious and life threatening infection, 36.0% were not sure of their experience and 23% had no fear of HIV. 33.8% respondents experienced mild to moderate level of burden, 27.2% respondents experienced moderate to severe level of burden while 15.7% experienced severe burden. A Chi Square value of 68.2 at P < 0.05 was obtained showing a significant relationship between fear of susceptibility and caregivers burden. This paper discusses the implications of these findings for nursing and health care and recommends the implementation of educational opportunities to allay fears and minimize caregiver burden among nurses and other health care professionals.